Understanding cross-national differences in unit non-response: the role of contact data - Annelies G. Blom; Peter Lynn; Annette Jäckle (University of Essex, Institute for Social and Economic Research (ISER), 2008)
This paper showcases ways in which contact data can provide useful auxiliary information to study non-response and devise new strategies for statistical adjustment and fieldwork specification in cross-national surveys. We propose a typology of the processes generating contact data and discuss their implications for the utility for methodological research. We also propose criteria for the comparability of contact data in cross-national surveys. To illustrate the potential of contact data, we review existing studies of non-response in cross-national studies. The paper ends with recommendations for cross-national studies, with the aim of increasing the widespread availability and use of standardised contact data.
Keywords: 330